Methodism empire of the spirit - Hempton, David; NetLibrary, Inc. (New Haven : Yale University Press, 2005)
Publisher description: The emergence of Methodism was arguably the most significant transformation of Protestant Christianity since the Reformation. This book explores the rise of Methodism from its unpromising origins as a religious society within the Church of England in the 1730s to a major international religious movement by the 1880s. During that period Methodism refashioned the old denominational order in the British Isles, became the largest religious denomination in the United States, and gave rise to the most dynamic world missionary movement of the nineteenth century. By the end of the nineteenth century, Methodism had circled the globe and was poised to become one of the fastest-growing religious traditions in the modern world.
Competition and symbiosis -- Enlightenment and enthusiasm -- The medium and the message -- Opposition and conflict -- Money and power -- Boundaries and margins -- Mapping and mission -- Consolidation and decline -- Methodism's rise and fall.
Includes bibliographical references (p. [259]-268) and index.
Electronic reproduction.
Keywords: Methodism -- History -- 18th century; Methodism -- History -- 19th century; Methodisme; Electronic books